Pengaruh Metode Dalcroze Melalui Aplikasi Meludia Melody - Ear Training Terhadap Kepekaan Tinggi Rendah Nada - Lusiani, Linda; Maulana, Maulana; Julia, Julia (Jurnal Pena Ilmiah, 2019)
The low sensitivity tones of students in elementary school is still a problem, especially in creating a sense of music. This study aims to determine the effect of the Dalcroze method through the Meludia Melody-Ear Training of sensitivity tones and differences with conventional learning; and to find students' responses to learning Dalcroze method through the Meludia Melody-Ear Training. The research design used was quasi-experiment with nonequivalent control group design. The subjects of this study were 2 rows in class IV at one of the primary schools in Cimanggung Subdistrict, Sumedang. The results showed that learning Dalcroze method through the Meludia Melody-Ear Training had a positive influence on sensitivity tones and 17% better than of conventional learning, and there was a positive response from students to learning Dalcroze method through the Meludia Melody-Ear Training. The conclusion is the Dalcroze method through the Meludia Melody-Ear Training can help improve sensitivity tones skills.